2021
DOI: 10.1001/jamanetworkopen.2021.28611
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Suicide Attempts Among Children in the Decade Before and During the COVID-19 Pandemic in Paris, France

Abstract: Recent studies have reported a deterioration in children's mental health since the start of the COVID-19 pandemic in 2020, with an increase in anxiety and mood disorders. 1 Rates of suicide ideation and suicide attempts among children were also higher when COVID-19-related stressors were heightened in 2020. 2,3 We aimed to better assess temporal trends in suicide attempts among children while adjusting for annual and seasonal fluctuations. We conducted a cross-sectional study of surveillance data collected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 5 publications
7
36
1
9
Order By: Relevance
“…Despite the growing evidence supporting the neurotropism of SARS‐CoV‐2, based on quantitative data for tropism, replication kinetics, and cell damage, this virus seems to cause modest neuropsychiatric manifestations in seroconverted children 6 . Finally, our results support further the impact of mitigation strategies on psychiatric symptom deterioration in children reported in early stages of the pandemic 1 …”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Despite the growing evidence supporting the neurotropism of SARS‐CoV‐2, based on quantitative data for tropism, replication kinetics, and cell damage, this virus seems to cause modest neuropsychiatric manifestations in seroconverted children 6 . Finally, our results support further the impact of mitigation strategies on psychiatric symptom deterioration in children reported in early stages of the pandemic 1 …”
Section: Discussionsupporting
confidence: 42%
“…Since the beginning of the SARS‐CoV‐2 pandemic, studies reported an increase in children's mental health issues 1 . Beyond the surge in environmental stressors such as restrictive isolation measures, the rapid actualization of psychiatric symptoms in children may be directly related to the SARS‐CoV‐2 through its neurotropism 2 .…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our study would have benefited from more detailed information on mental health issues to verify the reported rise of mental health issues in primary and secondary care elsewhere. 36 37 We were not able to reliably differentiate between face-to-face and virtual appointments in primary care, nor to assess comorbidities or vaccination status.…”
Section: Discussionmentioning
confidence: 96%
“…For example, studies reported relative unchanged ED attendance rates for urinary tract infections,3 5 and changes in the number of admissions for relatively infrequent safeguarding related injuries will have gone unnoticed. Likewise, our study would have benefited from more detailed information on mental health issues to verify the reported rise of mental health issues in primary and secondary care elsewhere 36 37. We were not able to reliably differentiate between face-to-face and virtual appointments in primary care, nor to assess comorbidities or vaccination status.…”
Section: Discussionmentioning
confidence: 99%